2021
DOI: 10.1128/mra.00093-21
|View full text |Cite
|
Sign up to set email alerts
|

Coding-Complete Genome Sequence and Phylogenetic Relatedness of a SARS-CoV-2 Strain Detected in March 2020 in Cameroon

Abstract: We describe the coding-complete genome sequence of a severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) strain obtained in Cameroon from a 58-year-old French patient who arrived from France on 24 February 2020. Phylogenetic analysis showed that this virus, named hCoV-19/Cameroon/1958-CMR-YAO/2020, belongs to lineage B.1.5 and is closely related to an isolate from France.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Finally, the antigens in the ELISA kits used were designed to target the original SARS-CoV-2 lineage that emerged in China. Several variants of the virus, such as the Omicron or delta lineages, have been reported in Cameroon during pandemic waves [65][66][67], and thus, it is likely that a few infection cases were missed as these antigens may not optimally detect antibodies against SARS-CoV-2 variants and that the seroprevalence is underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the antigens in the ELISA kits used were designed to target the original SARS-CoV-2 lineage that emerged in China. Several variants of the virus, such as the Omicron or delta lineages, have been reported in Cameroon during pandemic waves [65][66][67], and thus, it is likely that a few infection cases were missed as these antigens may not optimally detect antibodies against SARS-CoV-2 variants and that the seroprevalence is underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…Second, SARS-CoV-2 variants circulating in the country is also a plausible explanation ( Raman et al, 2021 ). Some studies reported the circulation of different SARS-CoV-2 variants in Cameroon ( Chouikha et al, 2022 ; Njouom et al, 2020 ). However, large epidemiological data on the extent of SARS-CoV-2 variants are still lacking in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the antigens in the ELISA kits used were designed to target the original SARS-CoV-2 lineage that emerged in China. Several variants of the virus, such as the Omicron or delta lineages, have been reported in Cameroon during pandemic waves [60][61][62], and thus, it is likely that a few infection cases were missed as these antigens may not optimally detect antibodies against SARS-CoV-2 variants and that the seroprevalence is underestimated.…”
Section: Discussionmentioning
confidence: 99%